Synthesis, characterization of porphyrin and CdS modified spherical shaped SiO2 for Reactive Red 120 degradation under direct sunlight - Krishnakumar, Balu (2020)
Initially, sphere shaped SiO2 was explored by adopting simple sol-gel method without any template. Later, the sphere like SiO2 was modified with cadmium sulfide (CdS) semiconductor and porphyrins. The formation of composites (CdS/SiO2-porphyrins) brought out by diverse characterization techniques that include XRD, Raman, FT-IR, FE-SEM, EDS, DRS and PL measurements. The photocatalytic activity of CdS/SiO2 was slightly influenced by porphyrins such as meso-tetra-phenyl-porphyrin (TPP) and 5,10,15,20-meso-tetra-(para-amino)-phenyl-porphyrin (TPAPP). The mechanism which has been proposed for Reactive Red 120 (RR 120) degradation by CdS/SiO2- porphyrins under sunlight.